2008
DOI: 10.1074/jbc.m706968200
|View full text |Cite
|
Sign up to set email alerts
|

Translational Efficiency of a Non-AUG Initiation Codon Is Significantly Affected by Its Sequence Context in Yeast

Abstract: Previous studies have shown that translation of mRNA for yeast glycyl-tRNA synthetase is alternatively initiated from UUG and a downstream AUG initiation codon. Evidence presented here shows that unlike an AUG initiation codon, efficiency of this non-AUG initiation codon is significantly affected by its sequence context, in particular the nucleotides at positions ؊3 to ؊1 relative to the initiation codon. A/A/R (R represents A or G) and C/G/C appear to be the most and least favorable sequences at these positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
55
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 42 publications
7
55
0
Order By: Relevance
“…Finally, based on a high throughput screen of start codon context nucleotides, Dvir et al (2013) reported a significant, but modest (,30%), impact of a 23 purine on reporter gene expression. At odds with these studies, flanking nucleotides have been shown to be important in selection of the non-AUG start codon on the GRS1 mRNA (Chen et al 2008) as well as in the selection of alternate AUG start codons on the MOD5 and CCA1 mRNAs (Werner et al 1987;Slusher et al 1991;Wolfe et al 1994). In addition, the poor start codon context (C 23 GUAUG) of the SUI1 gene encoding translation factor eIF1 in yeast impairs expression and enables autoregulation due to the role of eIF1 in start codon selection (Martin-Marcos et al 2011).…”
Section: Mrna Features In Translation Initiationmentioning
confidence: 80%
See 1 more Smart Citation
“…Finally, based on a high throughput screen of start codon context nucleotides, Dvir et al (2013) reported a significant, but modest (,30%), impact of a 23 purine on reporter gene expression. At odds with these studies, flanking nucleotides have been shown to be important in selection of the non-AUG start codon on the GRS1 mRNA (Chen et al 2008) as well as in the selection of alternate AUG start codons on the MOD5 and CCA1 mRNAs (Werner et al 1987;Slusher et al 1991;Wolfe et al 1994). In addition, the poor start codon context (C 23 GUAUG) of the SUI1 gene encoding translation factor eIF1 in yeast impairs expression and enables autoregulation due to the role of eIF1 in start codon selection (Martin-Marcos et al 2011).…”
Section: Mrna Features In Translation Initiationmentioning
confidence: 80%
“…Likewise, all possible single nucleotide substitutions at the AUG start codon of a HIS4-lacZ reporter lowered expression to #2% of the AUG control . However, the mRNAs encoding glycyl (Grs1) and alanyl (Ala1) tRNA synthetases initiate at both AUG and non-AUG codons (Chang and Wang 2004;Tang et al 2004;Chen et al 2008). Whereas the cytoplasmic synthetases initiate at an AUG start codon, the extended, mitochondrial enzymes initiate at upstream codons: UUG for Grs1 (Chen et al 2008) and ACG for Ala1 (Tang et al 2004).…”
Section: Mrna Features In Translation Initiationmentioning
confidence: 99%
“…Adenines at positions Ϫ3 to Ϫ1 relative to AUG are highly preferred among genes in Saccharomyces species (44), and there is evidence that A Ϫ3 -A Ϫ2 -(A/G) Ϫ1 -AUG is the optimal context for initiation in Saccharomyces cerevisiae (7). Saccharomyces species resemble other eukaryotes in displaying poor context for the AUG codon at the eIF1 gene (SUI1), C Ϫ3 -G Ϫ2 -U Ϫ1 -AUG, which matches at Ϫ3 and Ϫ2 a highly unfavorable sequence context identified in S. cerevisiae, of C Ϫ3 -G Ϫ2 -C Ϫ1 -AUG (7).…”
Section: Metmentioning
confidence: 99%
“…Nonetheless, three yeast genes, GRS1 (one of the two glycyl-tRNA synthetase (GlyRS) genes in S. cerevisiae) (11), ALA1 (the only alanyl-tRNA synthetase (AlaRS) gene in S. cerevisiae) (12), and CARP2A (the gene coding for acidic ribosomal protein P2A in Candida albicans) (25), have recently been reported to use naturally occurring non-AUG triplets as translation initiators. Moreover, a very recent study suggested that the translational efficiency of non-AUG initiation codons is significantly affected (up to 32-fold) by nucleotides at its relative Ϫ3 to Ϫ1 position, and, to a lesser extent, ϩ4 (26). The nucleotide at position Ϫ3 is the most influential one.…”
mentioning
confidence: 99%
“…The nucleotide at position Ϫ3 is the most influential one. AARuugA (R represents A or G; uug represents a non-AUG initiation codon) appears to be the most favorable sequence context for a non-AUG initiation site (26).…”
mentioning
confidence: 99%